2021
DOI: 10.1183/23120541.00942-2020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of comprehensive genotyping specimens from radial endobronchial ultrasonography and electromagnetic navigation bronchoscopy

Abstract: IntroductionMini-invasive bronchoscopic techniques (such as radial endobronchial ultrasonography (rEBUS) and electromagnetic navigation (EMN)) have been developed to reach the peripheral lung but result in small samples. The feasibility of an adequate molecular testing from these specimens has been very little studied.MethodsWe retrospectively reviewed EMN and rEBUS procedures performed in patients diagnosed with lung cancer in our institution in 2017 and 2018. We analysed the sensitivity for rEBUS and EMN and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Fielding et al ( 20 ) achieved high concordance rates in detecting mutations between smeared cytology and cell block and showed that DNA extracted from smears has higher rates of mutations than DNA obtained by cell block. Robin M et al ( 21 ), using both cytology and histology samples, were able to genotyping the tumor in 69.1% and to evaluate PD-L1 expression in 94% of 331 patients who underwent transbronchial approach to lung tumor with the guidance of rEBUS or electromagnetic navigation. However, in that study the cytological material was obtained only by brushing and catheter rinse.…”
Section: Discussionmentioning
confidence: 99%
“…Fielding et al ( 20 ) achieved high concordance rates in detecting mutations between smeared cytology and cell block and showed that DNA extracted from smears has higher rates of mutations than DNA obtained by cell block. Robin M et al ( 21 ), using both cytology and histology samples, were able to genotyping the tumor in 69.1% and to evaluate PD-L1 expression in 94% of 331 patients who underwent transbronchial approach to lung tumor with the guidance of rEBUS or electromagnetic navigation. However, in that study the cytological material was obtained only by brushing and catheter rinse.…”
Section: Discussionmentioning
confidence: 99%
“…One report evaluated feasibility of NGS and PD-L1 testing from samples obtained via rEBUS and ENB procedures. PD-L1 testing was successfully performed on 94% (n = 232) of cases [ 66 ]. A smaller cohort underwent subsequent surgical resection with perfect concordance among the 50% threshold (n = 15), whereas the >1% threshold identified three false negative cases (n = 8) from bronchoscopy specimens [ 66 ].…”
Section: Tissue Specimen and Diagnostic Testingmentioning
confidence: 99%
“…PD-L1 testing was successfully performed on 94% (n = 232) of cases [ 66 ]. A smaller cohort underwent subsequent surgical resection with perfect concordance among the 50% threshold (n = 15), whereas the >1% threshold identified three false negative cases (n = 8) from bronchoscopy specimens [ 66 ]. Unfortunately, exhausted tissue, leading to unacceptable NGS analysis, affected 30.9% (n = 188) of cases, disproportionately impacting early-stage disease [ 66 ].…”
Section: Tissue Specimen and Diagnostic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in approximately 30% of cases, these samples are noncontributory for genomic analysis owing to a lack of available tumor tissue. 5 , 6 , 7 In this context, ctDNA analysis could represent an alternative for genomic characterization.…”
Section: Introductionmentioning
confidence: 99%